MORPHO-, DENSITOMETRIC ANALYSIS OF THE DYNAMIC VARIABILITY OF BONE TISSUE OF THE CORONOID PROCESSES OF THE HUMAN MANDIBLE, DEPENDING ON THE LOSS OF THE MASTICATORY GROUP OF TEETH - Yaremchuk, N.I.; Oshurko, A.P.; Oliinyk, I.Yu.; Herasym, L.M.; Student, V.O. (World of Medicine and Biology, 2023)
The purpose of the study was to establish morphological variability of the macro- and microstructure of the bone tissue of the coronoid processes of the human mandible depending on the loss of the masticatory group of teeth in the I and II age periods of postnatal ontogenesis. The method of computed tomography with the Ez3D-i software (5.1) was used to study qualitatively homogeneous totals – quantitative indicators that determine the morphometric values and density of bone tissue in conventional gray units, a detailed analysis of the structure of the bone tissue of the coronoid processes of the left and right sides (n=136). The results of the study present quantitative morphometric values in individuals with limited and final dentition defects obtained in the areas of the coronoid processes exposed to the primary multifactorial pathoetiological influence, which have a negative direction on both sides when compared between the I and II age periods. In the case of acquired terminal defects of the dentition, the morphometric values of the base of the coronoid processes increase and are synchronized with the comparison group (mandibular angle quadrant). However, the densitometric variability of the bone tissue of the coronoid processes of the human mandible does not have a stable upward or downward trend.